2010
DOI: 10.3945/ajcn.2010.29306
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin genotype modifies the association between dietary vitamin C and serum ascorbic acid deficiency

Abstract: Background: Haptoglobin (which is encoded by the Hp gene) is a hemoglobin-binding protein that has antioxidant properties and a common polymorphism that consists of 2 structurally different alleles: Hp1 and Hp2. The capacity of Hp2 to inhibit oxidation and vitamin C depletion is less than that of Hp1, but the influence on vitamin C requirements remains unknown. Objective: This study aimed to determine whether the Hp polymorphism modifies the association between dietary vitamin C and serum ascorbic acid deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…Unlike Hp1 carriers, Hp2 homozygotes had lowest serum vitamin C concentrations when dietary vitamin C intake is insufficient. Thus, Hp1 has a greater antioxidant capacity preventing hemoglobin-ironrelated vitamin C oxidation and depletion [164].…”
Section: Folate Deficiencymentioning
confidence: 99%
“…Unlike Hp1 carriers, Hp2 homozygotes had lowest serum vitamin C concentrations when dietary vitamin C intake is insufficient. Thus, Hp1 has a greater antioxidant capacity preventing hemoglobin-ironrelated vitamin C oxidation and depletion [164].…”
Section: Folate Deficiencymentioning
confidence: 99%
“…In this study, Cahill and El-Sohemy showed a gene-diet interaction on the serum ascorbic acid concentration. In contrast to carriers of the Hp 1 allele with a greater antioxidant capacity, Hp 2-2 subjects had an increased risk of deficiency if they did not meet the RDA for vitamin C (Cahill and El-Sohemy 2010). Hp acts to prevent the oxidative and toxic effects of the iron-containing heme in Hb (Na et al 2005).…”
mentioning
confidence: 99%
“…Hp acts to prevent the oxidative and toxic effects of the iron-containing heme in Hb (Na et al 2005). The ascorbic acid stability in body fluids is lower in Hp 2-2 individuals (Cahill and El-Sohemy 2010;Delanghe et al 2007;Sadrzadeh and Eaton 1988;Langlois et al 1997). Hp 2-2 subjects are less efficient in removing free Hb from the plasma, which may favor an iron-mediated vitamin C depletion (Langlois et al 1997;Delanghe and Langlois 2002).…”
mentioning
confidence: 99%
See 2 more Smart Citations